2017
DOI: 10.1038/srep44070
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Effects of Nanoparticles for Cooling down Ultracold Neutrons

Abstract: Due to quantum coherence, nanoparticles have very large cross sections when scattering with very cold or Ultracold Neutrons (UCN). By calculating the scattering cross section quantum mechanically at first, then treating the nanoparticles as classical objects when including the rotational effects, we can derive the associated energy transfer. We find that rotational effects could play an important role in slowing down UCN. In consequence, the slowing down efficiency can be improved by as much as ~40%. Since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Beyond its traditional calcium-related effects on the bone health, vitamin D is closely related to the occurrence and development of nonskeletal system diseases [ 2 ]. A large number of experimental and clinical evidence have indicated that vitamin D may be negatively correlated with autoimmune diseases [ 3 ], tumor [ 4 ], infectious disease [ 5 ], hypertension [ 6 ], T2DM [ 7 ], metabolic syndrome [ 8 ], and cardiovascular disease (CVD) [ 9 ]. Diabetic macroangiopathy is a major chronic complication and a leading cause of death in patients with T2DM, and its main pathological change is atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its traditional calcium-related effects on the bone health, vitamin D is closely related to the occurrence and development of nonskeletal system diseases [ 2 ]. A large number of experimental and clinical evidence have indicated that vitamin D may be negatively correlated with autoimmune diseases [ 3 ], tumor [ 4 ], infectious disease [ 5 ], hypertension [ 6 ], T2DM [ 7 ], metabolic syndrome [ 8 ], and cardiovascular disease (CVD) [ 9 ]. Diabetic macroangiopathy is a major chronic complication and a leading cause of death in patients with T2DM, and its main pathological change is atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%